People trafficking in Australia - Jacqueline Joudo Larsen
The clandestine nature of trafficking in persons means that there is little reliable data about the nature and extent of the crime; however, a picture is emerging of the nature of people trafficking as the number of prosecutions grows. Few of the cases identified in Australia to date fit the traditional stereotypes of the forced movement and confinement of trafficked persons by traffickers. This paper summarises what is currently known about the nature of people trafficking in Australia. It includes an examination of how the reality of people trafficking compares with community perceptions of the crime. The authors note the need to establish reliable data-driven monitoring systems to better assess the nature and extent of trafficking into Australia, and the need to educate the Australian community to improve their understanding, given the important role they play in identifying and supporting trafficking victims